Pulmonary arteriovenous malformation with metal allergy. Issue 3 (10th March 2021) - Takase, Yoshiaki; Nakano, Sachiko; Yamaki, Ei; Kawashima, Osamu
Abstract : We present a rare case of single pulmonary arteriovenous malformation (PAVM) with multiple metal allergies, including for platinum. A 47-year-old woman presented to our hospital without any symptoms. Enhanced computed tomography showed a single PAVM in S6 of the right lung. Interviews prompted us to suspect a history of palmoplantar pustulosis associated with metal dental filling. Dermatology patch tests for metal allergy were positive for platinum, cobalt, tin and potassium dichromate. The first choice of treatment for PAVM is endovascular treatment using a metal coil. Since the coil is composed of platinum alloy, we performed partial lung resection for PAVM without metal implants. Although metal allergy is rare for endovascular treatment, it causes an additional stress of removal of causative metal or long-term steroidal treatment. Therefore, for single PAVM with multiple metal allergies to the implants, surgical treatment without metal implants should be considered.